The impact of parenting stress among fathers on children’s negative emotional behaviors - Mil, Silvie; Wulandari, Dewi Wahyu (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
This study aims to examine the impact of parenting stress experienced by fathers on children’s negative emotional behavior. This cross-sectional study involved 180 fathers with children aged 4-6 years selected using a non-probability sampling method. Data were collected through questionnaires administered via Google Forms. Data validity and reliability were assessed using expert judgment and field testing. Data were analyzed using the Smart PLS (Partial Least Squares) through outer model analysis, inner model analysis, and hypothesis testing. The results showed that 56.1% of children’s negative emotional behavior was influenced by parenting stress experienced by fathers. The results suggest that fathers, as heads of households, should adopt positive parenting practices and eliminate stressors while caring their children.